O desafio da avaliação de resultados em Comunicação Organizacional - Galerani, Gilceana Soares Moreira (Organicom, 2005)
This article presents literature concepts pertaining to evaluations in Communication, discusses the utilization of the term “control” in this area, describes planning as an essential requirement to adequately measure the results, and comments on two evaluation models, slightly approaching their application in two organizations in Brazil.